Measuring labor and delivery unit culture and clinicians' attitudes toward birth: Revision and validation of the Labor Culture Survey. Issue 2 (8th November 2018) - White VanGompel, Emily; Perez, Susan; Wang, Chi; Datta, Avisek; Cape, Valerie; Main, Elliott
Abstract: Background: Cesarean delivery rates in the United States vary widely between hospitals, which cannot be fully explained by hospital or patient factors. Cultural factors are hypothesized to play a role in cesarean overuse, yet tools to measure labor culture are lacking. The aim of this study was to revise and validate a survey tool to measure hospital culture specific to cesarean overuse. Methods: A panel of clinicians and researchers compiled an item bank from validated surveys, added newly created items, and performed four rounds of iterative revision and consolidation. Obstetricians, family physicians, midwives, anesthesiologists, and labor nurses were recruited from 79 hospitals in California. Exploratory factor analysis was used to reduce the number of survey items and identify latent constructs to form the basis of subscales. Confirmatory factor analysis examined reliability in 31 additional hospitals. Poisson regression assessed associations between hospitals' mean score on each individual item and cesarean rates. Results: A total of 1718 individuals from 70 hospitals were included in the exploratory factor analysis. The final Labor Culture Survey (LCS) consisted of 29 items and six subscales: "Best Practices to Reduce Cesarean Overuse, " "Fear of Vaginal Birth, " "Unit Microculture, " "Physician Oversight, " "Maternal Agency, " and "Cesarean Safety." Conclusions: The revised LCS is a valid and reliable tool to measure constructs shown to be associated with cesarean rates. These findings support prior research that has shown that hospital culture is measurable, and that clinician attitudes are predictive of clinician behaviors. Unique to our survey is the construct of labor and delivery unit microculture.